ANALYSIS OF TWO YEARS CASES OF ECTOPIC PREGNANCY - Islam, Ansa; Fawad, Aneesa; Shah, Azmat Ali; Jadoon, Humaira; Sarwar, Irum; Abbasi, Aziz-un-Nisa (Journal of Ayub Medical College Abbottabad, 2017)
Background: Ectopic pregnancy is the leading cause of pregnancy related deaths in the first trimester. The aim of this study was to evaluate the frequency of risk factors, clinical presentation, diagnostic methods and site of ectopic pregnancy Methods: This descriptive cross sectional study was conducted in Gynaecology and Obstetrical Unit-A of Ayub Teaching Hospital Abbottabad from 1st October 2013 to 31stOctober 2015. All women diagnosed with ectopic pregnancy were included in the study. A predesigned proforma was used to record the details about demographic features, risk factors, clinical features at presentation, diagnostic methods and site of ectopic pregnancy. Results: Out of total 6675 patients admitted during the study period, 45 cases of ectopic pregnancy were diagnosed with frequency of ectopic pregnancy to be 0.65%. Mean age of the patients was 28.98±5.525. Majority of patients were primigravida14(31.3%), 9 (20.0%) gravida 2, 5 (11.1%) gravida 3, 4 (8.8%) gravida 4, 7 (15.5%) gravida 5, 6 (13.3%) found grand multi out of total 45 ectopic pregnancies, 45% of the patients had no identifiable risk factors, however history of infertility 20 (22.22%), history of Pelvic inflammatory disease (PID) 10 (22.22%), previous ectopic 2 (4.44%) and previous abdominal pelvic surgery 3 (6.67%) were identified as common risk factors of 45 ectopic pregnancies. Out of total 45 sufferers 23 (51.11%) were clinically diagnosed, 20 (44.44%) through abdominal ultrasound and 2(4.44%) through transvaginal ultrasound. The most frequent clinical presentation was amenorrhea 30 (66.67%) followed by abdominal pain 28 (62.22%), irregular vaginal bleeding 18 (40.00%), asymptomatic patients with routine ultrasound 18 (40.0%) and 10 (22.22%) presented in shock. Twenty-eight (62.2%) of the ectopic pregnancies were found in right sided fallopian tube and 17(37.8%) were found in left sided fallopian tube. The commonest site of ectopic pregnancy was ampulla 29 (64.44%) followed by 11 (24.44%) Isthmus, 4 (8.89%) fimbrial end and 1 (2.22%) were rudimentary horn of uterus out of total 45 ectopic pregnancies. Evidence of 32 (71.1%) patients with ruptured ectopic was recorded. Thirteen (28.9%) were unruptured ectopic. Conclusion: Amenorrhea and abdominal pain are the most consistent features of ectopic pregnancy. Keywords: Ectopic pregnancy; Clinical presentation; Analysis of two years